20.6k views
3 votes
Solve the equation. 5y-7+y = -(y+3y).
Show steps please. ​

User Jerry An
by
5.2k points

1 Answer

7 votes

Answer:

10y-7=0

Explanation:

5y-7+y= -(y+3y)

first you distribute the -1 into the parenthesis

5y-7+y = -y-3y

then you have to get y on a side by itself. start by adding +y to both sides. This cancels out the -y on the left side leaving you with:

6y-7+y=-3y

next you add +3y to both sides, canceling out the -3y on the left and leaving you with:

9y-7+y=0

combine the +y and 9y and your answer is:

10y-7=0

User Koyaanisqatsi
by
5.0k points